Assessment of population exposure to Polycyclic Aromatic Hydrocarbons (PAHs) using integrated models and evaluation of uncertainties. (January 2015) - Gariazzo, Claudio; Lamberti, Mafalda; Hänninen, Otto; Silibello, Camillo; Pelliccioni, Armando; Porta, Daniela; Cecinato, Angelo; Gherardi, Monica; Forastiere, Francesco
Abstract: Polycyclic Aromatic Hydrocarbons (PAHs) are considered among the most dangerous air pollutants due to their carcinogenic and mutagenic characteristics. Populations living in urban area are exposed to these pollutants because of their proximity to the emission sources. However, the spatial and temporal characteristics of PAHs concentrations in such areas are not well known. An integrated modeling approach is here presented to estimate exposure to PAHs content in PM2.5 of children and elderly people living in the city of Rome, Italy. It is based on a microenvironment approach in which exposure is estimated by accounting for PAHs concentrations experienced by the target population in the most visited living environments. The model uses data provided by the EU LIFE + EXPAH project: indoor/outdoor PAHs concentrations collected in homes, schools, cars, buses and offices to derive PAHs infiltration factors for the specific environments; time activity to identify daytime profiles of the target population and information on the prevailing living environments; ambient PAHs concentration fields. The latter have been obtained by integrating Chemical Transport Model (CTM) results with measurements collected by the EXPAH project. Uncertainties in the estimation of PAHs exposure has been evaluated by applying a Monte Carlo statistical approach using probability density function based on observed exposure parameters. Results were calculated for one year (June 2011–May 2012). The downtown area was found to be the most contaminated one with concentrations up to 2 ± 1 and 0.6 ± 0.2 ng/m 3, on an annual basis, respectively for ∑4 PAHs (e.g. B[a]P, B[b]F, B[k]F and indeno(1, 2, 3-cd)pyrene) and B[a]P. Results do not exhibit significant differences on ∑4 PAHs exposure between children and elderly people, mainly due to the prevalence of indoor microenvironments in the time activity data, and to the little difference in the indoor/outdoor infiltration. Seasonality was identified as an important factor contributing to the overall exposure. The higher PAHs emissions during the heating period determine a greater exposure during winter. Homes have been identified as the microenvironments that most contribute to PAHs exposure followed by schools. Graphical abstract: Highlights: PAHs exposures during heating season are higher than in non-heating season. Indoor environments play a dominant role in the daily PAHs exposure. Infiltration reduces indoors PAHs exposure levels by 10–40% depending on the living environment. PAHs exposures between elderly and children did not vary substantially. Based on PAHs modeling results the highest exposure occur in the city center.